2002
DOI: 10.1159/000047769
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Antibodies in the Acute Phase of Cerebral Ischaemia in Young Adults: A Descriptive Study of 139 Patients

Abstract: A total of 139 young stroke patients were consecutively examined and tested for antiphospholipid antibodies (APLA) to evaluate the role of these antibodies in cerebral ischaemia before the age of 45. APLA were found in 28.8% of patients. Two factors, hypertriglyceridaemia and alcohol abuse, were significantly more frequent in patients with a positive APLA test. The demographic characteristics, other risk factors, history of prior thrombotic events and distribution of aetiopathogenic types of cerebral ischaemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 20 publications
0
19
0
2
Order By: Relevance
“…372 The association between APL antibodies and stroke is strongest for young adults (Ͻ50 years of age). 373,374 In the Antiphospholipid Antibodies in Stroke Study (APASS), 9.7% of ischemic stroke patients and 4.3% of control subjects were anticardiolipin positive. 375 In the Antiphospholipid Antibodies in Stroke substudy of WARSS (WARSS/APASS), APL antibodies were detected in 40.7% of stroke patients, but they had no significant effect on the risk of stroke recurrence.…”
Section: Antiphospholipid Antibodiesmentioning
confidence: 99%
“…372 The association between APL antibodies and stroke is strongest for young adults (Ͻ50 years of age). 373,374 In the Antiphospholipid Antibodies in Stroke Study (APASS), 9.7% of ischemic stroke patients and 4.3% of control subjects were anticardiolipin positive. 375 In the Antiphospholipid Antibodies in Stroke substudy of WARSS (WARSS/APASS), APL antibodies were detected in 40.7% of stroke patients, but they had no significant effect on the risk of stroke recurrence.…”
Section: Antiphospholipid Antibodiesmentioning
confidence: 99%
“…Given the low diagnostic yield, routine evaluation for venous hypercoagulability was not performed unless suggested by a clinical history of hypercoagulable states, e.g., a family history of venous thrombosis, thrombosis at an early age (Ͻ 45 years) with pulmonary embolus, recurrent venous thrombosis, and coumadin-induced thrombosis [6]. Similarly, the presence of a primary antiphospholipid syndrome was not routinely assessed, unless additional clinical features were present, e.g., a history of recurrent thromboses or fetal loss, thrombocytopenia, or livedo reticularis [7].…”
Section: Study Populationmentioning
confidence: 99%
“…They have been associated with recurrent episodes of arterial or venous thrombosis or both, recurrent fetal loss, neurological diseases and possible thrombocytopenia. 3,4 Stroke is defined as a syndrome of rapidly developing clinical symptoms and signs of focal (or global) loss of cerebral functions, with symptoms lasting 24 hours or longer or resulting in death with no apparent cause other than of vascular origin 5 . The prevalence of stroke in Nigeria is on the increase.6, 7 Osuntokun et al6 reported a crude prevalence of 58 per 100,000 of the population and Danesi et al 7 in a more recent studies reported a rate of 1.14 per 1,000.…”
Section: Introductionmentioning
confidence: 99%